Cylicostephanus scharchui sp. n. (Nematoda: Strongyloidea) from Equids of Mongolia - Ochirkhuu Ulambayar (Mongolian Journal of Biological Sciences)
The present paper describes a new strongylid nematode belonging to the genus Cylicostephanus Ihle, 1922 (Strongyloidea, Cyathostominae), from Asiatic wild ass (Khulan) and domestic horses in Mongolia. The external leaf-crown (ELC) of Cylicostephanus scharchui sp. n. consists of approximately 12 elements and the internal leaf-crown (ILC) of approximately 36 elements. The buccal capsule is cylindrical, circular in cross-section, and slightly deeper than wide. A long dorsal gutter extends from the floor of the buccal capsule closely to base of ILC. The duct of the dorsal esophageal gland opens at the tip of the dorsal gutter. The tail of females is short, and the vulva is close to the anus. The buccal capsule and dorsal gutter are most similar to those of Cylicostephanus calicatus, but differ significantly in size of dorsal gutter and relative width and depth of the buccal capsule as well as characteristics of the leaf-crowns.